AN ANALYSIS OF METAPHOR ON POLITICAL ISSUES IN THE JAKARTA POST NEWSPAPER - Damayanti Z.A, Rahmadina; ', Jismulatif; ', Marzuki (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research aims to identify and describe the types of metaphor used by journalist on political issues in The Jakarta Post newspaper and to discover the dominant type of metaphor. This is a qualitative research with analysis method. Five copies of The Jakarta Post newspaper which from May 15th 2017 edition until May 19th 2017 edition were used and analyzed on political issues only. There were 27 collected data from 18 political issues that contained metaphor. Ontological metaphor appears 16 times, structural metaphor appears 7 times and orientational metaphor appears 4 times. Based on the research findings, it can be concluded that ontological metaphor is the dominant type of metaphor that journalist used to write their opinion or to convey the news in political issues. It is suggested that future researchers who are interested in metaphor need to deepen analysis since political world and journalists keep changing through times so that they can provide new results.Keywords: Metaphor, metaphor in newspaper, The Jakarta Post.